In Silico Study of the Antibacterial Activity of Acalypha indica L. Compounds Against Staphylococcus aureus DNA Gyrase Protein - Savitri, Lisa; Ihsan, Kharisul; Kasimo, Elfred Rinaldo (Biology, Medicine, & Natural Product Chemistry, 2026)
Flavonoids from Acalypha indica exhibit potential antibacterial activity against Staphylococcus aureus, particularly through inhibition of DNA gyrase B. This study evaluated molecular interactions of mauritanin, acalyphin, quercetin, and kaempferol using in silico approaches, including molecular docking, molecular dynamics simulation, and ADMET prediction. Docking results showed that mauritanin had the lowest binding energy (-8.5 kcal/mol) and formed stable interactions with key residues in the active site, corroborated by 50 ns molecular dynamics simulations. Pharmacokinetic and drug-likeness predictions indicated that mauritanin and acalyphin had favorable profiles, with high gastrointestinal absorption and low toxicity risk. The other flavonoids showed higher permeability across the central nervous system, potentially beneficial for CNS-targeted therapies. These findings support mauritanin as a promising lead compound for novel antibacterial agent development, warranting further in vitro and in vivo validation.